1999
DOI: 10.1111/j.1600-0897.1999.tb00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Type‐1 and Type‐2 Cytokines in Human Decidual Tissue and Trophoblasts from Normal and Abnormal Pregnancies Detected by Reverse Transcriptase Polymerase Chain Reaction (RT‐PCR)

Abstract: Overall, our findings suggest that there is a balance between type-1 and type-2 cytokines during pregnancy, which is mainly characterized by the expression of IFN-gamma (a type-1 cytokine) and IL-10 (a type-2 cytokine) at the maternal fetal interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 29 publications
0
21
0
2
Order By: Relevance
“…Indeed, previous studies focusing on gestational tissues have reported either no significant differences [59,62,183] or a significant reduction in IL-10 expression in the presence of labor when compared to controls [184][185][186]. Of note, Hanna et al [59] reported a labor-associated up-regulation of TNF-a and IL-1 expression in placental explants and freshly isolated cytotrophoblasts in contrast to an absence of appreciable changes in IL-10 expression [59].…”
Section: Il-10 In Spontaneous Labor At Termmentioning
confidence: 78%
“…Indeed, previous studies focusing on gestational tissues have reported either no significant differences [59,62,183] or a significant reduction in IL-10 expression in the presence of labor when compared to controls [184][185][186]. Of note, Hanna et al [59] reported a labor-associated up-regulation of TNF-a and IL-1 expression in placental explants and freshly isolated cytotrophoblasts in contrast to an absence of appreciable changes in IL-10 expression [59].…”
Section: Il-10 In Spontaneous Labor At Termmentioning
confidence: 78%
“…Besides Th cells, other sources of this cytokine could be natural killer, decidual, or endothelial cells. 22 The intracellular concentrations of IL-2 and IFN-y did not differ between preeclamptic and normotensive pregnant women. We observed a tendency toward lower cytokine expression among CD3+CD4+ and CD3+CD8+ cells from women with preeclampsia.…”
Section: Discussionmentioning
confidence: 98%
“…When the balance between ROS and protection mechanisms shifts toward prooxidant, excessive ROS will arise and damage will occur. Damage caused by free radicals (oxidative stress) and lipid peroxidation is involved in the pathophysiology of a various clinical circumstances [8]. Women who undergo abortions will have a significantly lower level of total thiol, ceruloplasmin, ascorbic acid, α-tocopherol, and erythrocyte glutathione than control group.…”
Section: Discussionmentioning
confidence: 99%
“…In the immunological pathway of Th1 there is an increase of embryotoxic IFN-γ, whereas in the immunological pathway of Th2 there is a decrease of IL-4 level. Vives et al [8] examined cytokine expression in the decidua and trophoblast tissue. The result showed a significantly increased level of IFN-γ in decidual tissue of women who undergo abortion.…”
Section: Discussionmentioning
confidence: 99%